Pengaruh Metode Tanya Jawab Terhadap Motivasi Belajar Pendidikan Agama Kristen Siswa Kelas VIII SMP Negeri 1 Kolang Kecamatan Kolang Kabupaten Tapanuli Tengah Tahun Pembelajaran 2023/2024 - Velby Rut Simbolon; Maria Widiastuti; Goklas J. Manalu; Robinhot Sihombing; Oloria Malau (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The aim of this research is to determine the effect of the question and answer method on the learning motivation for Christian Religious Education and Character Education of class VIII students at SMP Negeri 1 Kolang, Kolang District, Central Tapanuli Regency for the 2023/2024 academic year. The research method used is a research method using a quantitative approach with inferential descriptive data analysis. The population is all 115 students of class VIII of SMP Negeri 1 Kolang, Kolang District, Central Tapanuli Regency for the 2023/2024 Academic Year who are Christians and the research sample was determined to be 38 people, namely 35% of the total population using Random Sampling techniques. Data was collected using a positive closed questionnaire with 20 items for variable 05,n=38) = 0.320. b) Testing a significant relationship obtained a value of tcount= 3.410 > ttable(=0.05,dk=n-2=36)= 2.042. 2) Influence test: a) Regression equation test, obtained the regression equation Y ̂=